UJI AKTIVITAS GEL EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana L.) SEBAGAI PENYEMBUH LUKA BAKAR PADA KULIT PUNGGUNG KELINCI - Mutmainah -; Lia Kusmita; Ika Puspitaningrum (Media Farmasi Indonesia, 2014)
ABSTRACT Mangosteen is a skin shells discarded by consumers or may be called by the waste of agricultural products. Mangosteen rind contain xanthone, flavonoids, saponins and tannins that are thought to be potentially heal burn. The air of this study was to determine the effect of ethanolic extract of mangosteen rind with a concentration of 2,5%, 5%, 10 % of ethanol extract of mangosteen rind in the preparation of the gel on the healing of burns on the back of rabbits. The research is conducted using male rabbit which was divided into five groups, namely the group of positive control, negative control, mangosteen rind extract gel ethanol concentration of 2,5%, 5%, 10 %. Induction plates use iron burns with size of 2 cm is heated at a temperature of 100°C for 5 seconds, these gels are done every day until wound healing as seen from the time required for diameter shrink to the perfect closing wound. The results of pharmacological tests of statistical tests with increased concentrations of the extract showed a significant difference in each group viewed from a long healing (p <0.05). Physical characteristics of the test results showed that the concentration of the ethanol extract of mangosteen rind in a row with a concentration of 2,5%, 5%, 10% were able to increase the viscosity, pH, adhesion and lower dispersive power.